2019 Global Food Policy Report Launch and 2019 EAT-Lancet Report in The Netherlands - Fan, Shenggen (2019)
Shenggen Fan 2019 Global Food Policy Report and 2019 EAT-Lancet Report Co-Organized by Ministry of Foreign Affairs of the Netherlands and IFPRI JUN 4, 2019 - 02:30 PM TO 05:00 PM CEST